Eccles se mistisisme en kuhlendeck se boeddhisme as moontlike grondslag vir fisiologie - Pretorius, P. J. (Koers, 1986)
The discussion ranging around the issues of human worth, uniqueness, the typically human, spirituality and human freedom also includes the subject of Physiology. The sense and the meaning of physiological knowledge, foundations for ethical norms and religious functions of man are of cardinal importance for the subject philosophy of Physiology.